Sociodemographic, Electrophysiological, and Biochemical Profiles in Children with Attention Deficit Hyperactivity Disorder and/or Epilepsy - Sameh A. Abd El Naby; Yahya M. Naguib (Behavioural Neurology)
Attention deficit hyperactivity disorder (ADHD) is among the most prevalent neurobehavioral disorders affecting children worldwide. The prevalence of ADHD is higher in children with epilepsy. Despite the plethora of conducted work, the precise cause of ADHD is not identified yet. We studied here the sociodemographic, clinical, electrophysiological, and biochemical profiles of children with ADHD, epilepsy, and ADHD with epilepsy. Subjects were divided into 4 groups (25 child/group): I—control, II—ADHD, III—epilepsy, and IV—ADHD with epilepsy. Male to female ratio was significantly (p<0.05) higher in the ADHD (3.1) and ADHD with epilepsy (2.1) groups when compared to the control (1.08) or epilepsy (1.08) groups. Positive family history was significantly evident in patients with epilepsy and ADHD with epilepsy, but not in the control or ADHD groups. Speech development was significantly delayed in the ADHD and ADHD with epilepsy groups. EEG abnormalities were detected in patients with ADHD (12%) and ADHD with epilepsy (68%). Focal frontal activities were significantly detectable in the ADHD (100%) and ADHD with epilepsy (77.8%) groups, whereas focal temporal activity was significantly present in the epilepsy (83.3%) group. Serum ferritin was significantly lower in the ADHD group (110.27 ± 6.64 ηg/ml) when compared to the control (134.23 ± 14.82 ηg/ml), epilepsy (159.66 ± 33.17 ηg/ml), and ADHD with epilepsy (203.04 ± 50.64 ηg/ml) groups. Serum zinc was significantly higher in the ADHD, epilepsy, and ADHD with epilepsy groups (236.63 ± 20.89, 286.74 ± 43.84, and 229.95 ± 67.34 μg/dl, respectively), when compared to the control group (144.21 ± 17.40 μg/dl). Serum adenosine deaminase was insignificantly different among the groups. Our results indicate that gender and family history are significant moderators in the aetiology of ADHD and epilepsy or their comorbidity. We also demonstrated that EEG could be central in the assessment of ADHD with epilepsy cases. Serum ferritin and zinc alteration may contribute significantly in ADHD and epilepsy pathophysiology.